Una gran puzza di merda nell’aria. La performatività decoloniale del disgusto nel reading di Wissal Houbabi (Itinera, 2024)
Visceral, instinctive, aversive: disgust takes the form of a complex, often overwhelming sensation. It represents the risk of jeopardizing the integrity of a vague and illusory purity. Indeed, the expression of disgust appears as a firm claim to superiority over the other, considered inferior, inhuman and infectious. According to Tuija Saresmo and Urho Tulo- nen, populist rhetoric uses precisely disgust to emphasize the sharp distinction between the superior, i.e., white, and racialized subjects, legitimizing the implementation of poli- cies xenophobic discrimination. Disgust then becomes the necessary means of consoli- dating social order by exerting violence against supposedly defiling bodies.In Una gran puzza di merda nell’aria, Wissal Houbabi addresses the structural racism inherent in the construction of Italian culture, focusing specifically on the murder of Younes El Boussettaoui committed by Massimo Adriatici in Voghera in the summer of 2021. Beginning with the title of the performance, the artist uses terms that can be traced back to disgust to describe the attitude taken by the Northern League alderman, nauseated by the presence of a man of Moroccan origin, therefore different, homeless, that is, on the margins of civilized society, and suffering from mental disorders, therefore infectious. At the same time, however, disgust in Houbabi’s work takes on a an unprecedented decolo- nial connotation, restoring the revulsion felt by Bahijia El Boussetaoui, the victim’s sister, in front of the impunity of the crime committed by Adriatici, who returned to freedom after a brief period spent under house arrest.This paper, therefore, aims to investigate the performativity of disgust from a decolonial perspective, examining Houbabi’s work as a significant case study significant, especially in relation to today’s national context.
Keywords: Decoloniality, Performance, Disgust